Profile of children hospitalized in a burn treatment center - Priscila Santa de Moraes; Rosângela Aparecida Pimenta Ferrari; Flávia Lopes Sant'Anna; Jéssica Talita Mariana Wicthoff Raniero; Laís da Silva Lima; Tabatha de Freitas Moreira Santos; Mauren Teresa Grubisich Mendes Tacla (Universidade Federal de Goias, 2014)
A quantitative, retrospective and cross-sectional study to define the characteristics of pediatric hospitalization in a Burn Treatment Center between 2007 and 2011. There were 248 children burn victims hospitalized, of which 65.7% were male and 50.4% younger than three years of age. Approximately 58.0% of accidents occurred in autumn/winter. The main causative agent for those younger than three years was scalding (72.1%), and for those between 4 and 12 years old, direct flame contact (52.5%). 86.0% of burns were classified as second and third degree, predominately on upper limbs, torso and head. Mean hospitalization time was 14.8 days. Patients were discharged with improvement in 58.0% of cases, 38.0% were referred to rehabilitation and 4.0% died. Burns among the pediatric population can be avoided by investing in prevention campaigns, aimed especially at bringing awareness to families about the risk of child morbimortality and repercussions due to burns. doi: 10.5216/ree.v16i3.21968.